Contribution of mobile health applications to self-management by consumers: review of published evidence - Anderson, Kevin; Emmerton, Lynne (2016)
Objective: The aim of the present study was to review the contribution of mobile health applications (‘apps’) to consumers’ self-management of chronic health conditions, and the potential for this practice to inform health policy, procedures and guidelines. Methods: A search was performed on the MEDLINE, Cochrane Library, ProQuest and Global Health (Ovid) databases using the search terms ‘mobile app*’, ‘self-care’, ‘self-monitoring’, ‘trial’, ‘intervention*’ and various medical conditions. The search was supplemented with manual location of emerging literature and government reports. Mapping review methods identified relevant titles and abstracts, followed by review of content to determine extant research, reports addressing the key questions, and gaps suggesting areas for future research. Available studies were organised by disease state, and presented in a narrative analysis. Results: Four studies describing the results of clinical trials were identified from Canada, England, Taiwan and Australia; all but the Australian study used custom-made apps. The available studies examined the effect of apps in health monitoring, reporting positive but not robust findings. Australian public policy and government reports acknowledge and support self-management, but do not address the potential contribution of mobile interventions. Conclusions: There are limited controlled trials testing the contribution of health apps to consumers’ self-management. Further evidence in this field is required to inform health policy and practice relating to self-management.Objective. The aim of the present study was to review the contribution of mobile health applications (‘apps’) to consumers’ self-management of chronic health conditions, and the potential for this practice to inform health policy, procedures and guidelines. Methods. A search was performed on the MEDLINE, Cochrane Library, ProQuest and Global Health (Ovid) databases using the search terms ‘mobile app*’, ‘self-care’, ‘self-monitoring’, ‘trial’, ‘intervention*’ and various medical conditions. The search was supplemented with manual location of emerging literature and government reports. Mapping review methods identified relevant titles and abstracts, followed by review of content to determine extant research, reports addressing the key questions, and gaps suggesting areas for future research. Available studies were organised by disease state, and presented in a narrative analysis. Results. Four studies describing the results of clinical trials were identified from Canada, England, Taiwan and Australia; all but the Australian study used custom-made apps. The available studies examined the effect of apps in health monitoring, reporting positive but not robust findings. Australian public policy and government reports acknowledge and support self-management, but do not address the potential contribution of mobile interventions. Conclusions. There are limited controlled trials testing the contribution of health apps to consumers’ self-management. Further evidence in this field is required to inform health policy and practice relating to self-management.